Institutionalization of Intellectual Property on Resource-Saving Technologies and Materials: A Comparative Institutional Study of USA and Russia - INSHAKOVA, Agnessa; FROLOVA, Daniil; KAZACHENOK, Svetlana; MARUSCHAK, Irina (Journal of Advanced Research in Law and Economics, 2017)
The intellectualization of the prime factors of production as the determining inevitability of forming the innovative economy is accompanied by the intensification of involvement in the economic turnover of the results of scientific and scientific-technical activity and determines the special importance of intellectual property law. The economic relevance of the corresponding legal sector, as well as the empirical analysis of the practical activities of the authors, determined the research, which appeals to the process of the national lawmaking in this civil institution. In terms of the activities of the national economic entity LLC ‘GRUS’, which implements the production of high-tech materials, including nanomaterials, the balance between the exclusive rights of authors and investors in the innovative cross-border cooperation is considered. The authors comment on the novelty of civil law relating to the registration of the results of intellectual activity, as well as the special legal regime of dependent inventions, utility models and industrial designs. They investigate the problem of foreign patenting of domestic research results and developments, intended for export, and determine the ways of its solution.
Keywords: intellectual capital; high technology; intellectualization of prime factors of production; high-tech materials; nano materials; nanotechnology; innovative economic management; economic turnover of results of scientific and scientific-technical activity